Digital Transformation of Balian Tradition Among The Dayak Siang Community: A Phenomenological Analysis with an Artificial Intelligence Approach - Manik, Resmin; Jimmy, Andreas; Andriyanto, Yustinus Dwi (International Journal of Artificial Intelligence Research, 2024)
The Balian tradition represents a significant local wisdom within the Dayak Siang community in Puruk Cahu, Central Kalimantan. This tradition embodies deep-rooted spiritual and social values that have been integral to the local community's life. However, the existence of the Balian tradition is currently threatened by the increasingly rapid flow of modernity. This research aims to explore the potential utilization of Artificial Intelligence (AI) technology as a strategy for preserving the Balian tradition through digital transformation. Using qualitative methods and a phenomenological approach, data were collected through in-depth interviews and participatory observation. Informants in this study included Damang (Traditional Leaders), community leaders, church figures, academics, and young people concerned with preserving local culture. The results show that the Balian tradition contains rich philosophical values reflecting inter-subjective relationships, compassion, and strong mutual cooperation within the Dayak Siang community. This practice is also believed to connect humans, nature, and the spirit world. AI technology has the potential to document, analyze, educate, and disseminate information about local cultural heritage efficiently and affordably, thereby contributing to maintaining the existence of the Balian tradition amid modernization.